Ribautia lewisi sp. nov., a new centipede from Argentina with unusual tentorial process (Chilopoda: Geophilomorpha, Geophilidae) - Pereira, Luis Alberto (2013)
Ribautia lewisi sp. nov. (Chilopoda: Geophilomorpha, Geophilidae) is herein described and illustrated after the holotype (male), paratypes (males and females), and additional non type specimens from Northeastern Argentina (Mesopotamian region). The new species is characterized by having a cluster of coxal organs in each coxopleuron of the ultimate leg-bear-ing segment and a claw-like pretarsus in the ultimate legs, bearing a very unusual feature, in that the internal limbs of ten-torium have a conspicuous tooth-shaped sclerotized process directed inward. R. lewisi sp. nov. is only the second confirmed record of the genus Ribautia from Argentina, the other being R. jakulicai Pereira, 2007 from Northwestern re-gion of the country (Yungas biogeographical province).